APPLICATION OF STAD COOPERATIVE LEARNING MODEL TO INCREASE STUDENTS’ LEARNING OUTCOMES IN SOCIAL SCIENCE SUBJECT - Emi Emi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
This study aims to improve social studies learning outcomes for the fifth-grade students of SDN 15 Cakranegara in the 2018-2019 school year, totaling 28 people, consisting of 12 boys and 16 girls. The research method used is: Cooperative Learning Model Type Student Team Achievement Division (STAD) with data collection techniques in the form of observation and evaluation tests, then analyzed qualitatively by comparing the success rates between cycles. The results of this study indicate an increase in the number of students who complete learning or get a score of 70, namely 22 students in the first cycle to 25 students in the second cycle. An increase also occurred in the average value of the evaluation test given after the learning process was over, namely: 75 in the first cycle, to 83 in the second cycle. While the percentage of student learning completeness in each cycle, which is 79% in the first cycle, increased to 89% in the second cycle. In addition, the application of this method can also increase the activities of teachers and students which increase from cycle I to cycle II. This is evidenced by the percentage of teacher activity which increased from 75% in the first cycle to 87% in the second cycle. Increased student activity is indicated by 65% ​​in the first cycle, to 81% in the second cycle. The cooperative learning model of the Student Teams Achievement Division (STAD) type can improve the social studies learning achievement of fifth graders at SDN 15 Cakranegara for the 2018-2019 school year.